Peran Guru di SMPN 5 Lembang Jaya dalam Meningkatkan Aktivitas Siswa Melalui Media Pembelajaran pada Mata Pelajaran IPA - Helvita Roza; Chairul Amri; Ratih Komala Dewi; Darmanella Dian Eka Wati; Afrahamiryano; Irwan Hanafi (LPPM Universitas Ekasakti, 2024)
Education plays a vital role in the development of individuals and society. While the focus on educational quality often centers around the role of teachers, other factors such as the curriculum, students, and instructional media also have significant impacts. This research aims to identify the role of teachers at SMPN 5 Lembang Jaya in enhancing student engagement through instructional media in the subject of Science. The research utilizes a qualitative descriptive method and a case study approach at SMPN 5 Lembang Jaya. Data were collected through observation, interviews, and documentation with Science teachers. The findings indicate that teachers serve as educators, facilitators, and motivators. They create an effective classroom environment, provide engaging instructional media, and offer encouragement and recognition to students.The conclusion of this research underscores the crucial role of teachers in enhancing student engagement through Science instructional media. Teachers should continuously improve their skills in utilizing instructional media, and school administrators can support this by providing additional resources. Furthermore, students should be encouraged to be more motivated in their learning endeavors. These suggestions aim to enhance the quality of education at SMPN 5 Lembang Jaya.